Antagonistic potentials of some soil fungi against three post‐harvest pathogenic fungi of Carica papaya L. (Dhaka University Journal of Biological Sciences, 2019)
Four antagonistic fungi were isolated from the papaya field soil by serial dilution and were identified as Aspergillus flavus Link., A. fumigatus Fresenius, A. niger van Tiegh. and Trichoderma viride Pers. The soil fungi were selected to evaluate their antagonistic potentiality against the three postharvest pathogenic fungi of Carica papaya L. following "dual culture colony interaction” and volatile and non-volatile metabolites. In dual culture colony interaction, out of four soil fungi, T. viride showed the highest growth inhibition on C. gloeosporioides (84.28%), F. nivale (95.23%) and Fusarium sp. (87.15%). On the other hand A. niger showed the highest growth inhibition on C. gloeosporioides (77.39%), F. nivale (98.63%) and Fusarium sp. (35.05%). The maximum inhibition of radial growth of C. gloeosporioides (77.64%), F. nivale (58.76%) and Fusarium sp. (79.37%). were observed in case of T. viride owing to the volatile metabolites. Whereas the maximum inhibition of radial growth of C. gloeosporioides (58.23%), F. nivale (37.43%) and Fusarium sp. (82.31%) were observed in case of A. niger owing to the volatile metabolites. The maximum inhibition of radial growth of C. gloeosporioides (90.90%), F. nivale (89.13%) and Fusarium sp. (76.84%) were observed in case of T. viride owing to the effect of non-volatile metabolites. The maximum inhibition of radial growth of C. gloeosporioides (92.42%), F. nivale (73.01%) and Fusarium sp. (68.67%) were observed in case of A. niger owing to the effect of non-volatile metabolites. Trichoderma viride and A. niger may be exploited commercially as a biocontrol agent against anthracnose and fruit rot pathogens of papaya.Dhaka Univ. J. Biol. Sci. 28(1): 1-7, 2019 (January)